Corporate liability for bribery—in favour of systematic approach. Issue 3 (2nd July 2020) - Harris, Hannah
ABSTRACT: This article argues in favour of a systematic approach to corporate liability for all bribery offences, including commercial bribery. Australia's Banking Royal Commission and numerous international corruption scandals have demonstrated a 'culture of corruption' in our corporations. Australia has taken steps to strengthen the laws that criminalise foreign bribery, but there has been less interest in addressing the legal approach to commercial bribery. This article uses a comparative methodology to demonstrate that many of the arguments in favour of strict liability for corporations in cases of public sector and foreign bribery can also be applied to commercial bribery. A comparison of anti-bribery laws across common-law jurisdictions (Australia, United Kingdom and United States) illustrates opportunities to streamline the legal approach. Streamlining the legal approach to corporate liability for all bribery offences, including commercial bribery, will simplify compliance and incentivise adoption of policies and practices aimed at reducing corrupt conduct in commercial transactions. This, in turn, will result in meaningful changes in corporate culture.